The Effect of Financial Development on Economic Growth in East Kalimantan in 2013-2021 - Raihan Hibatullah; Aisyah Fitri Yuniasih S.S.T., S.E., M.Si. (Politeknik Statistika STIS, 2023)
Indonesia has a strong commitment to realizing inclusive and sustainable economic growth. The 8th SDGs achievement program has become the government's main program implemented in all provinces in Indonesia. The economic growth of a region can be measured using growth of Gross Regional Domestic Product (GRDP). East Kalimantan is one of the largest GRDP contributing provinces in Indonesia with the mining and quarrying sector as the leading sector. However, economic growth in the province is still relatively low and has never reached national figures. This forces the government to consider and develop the potential of other sectors. The Fiscal Policy Agency stated that the financial sector with its development has driven Indonesia's economic growth in the last few decades. This study aims to analyze the general picture of economic growth and financial development as well as the influence of financial development factors on the economic growth of districts/cities in East Kalimantan Province in 2013-2021. The analytical method used in this research is panel data regression. The results obtained are number of bank offices per population, number of cooperatives per population, credit distribution per GRDP, and number of workers have a positive effect on the economic growth of districts/cities in East Kalimantan Province in 2013-2021.